2020
DOI: 10.1136/bmjresp-2020-000646
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of admitted patients infected with SARS-CoV-2 in Uganda

Abstract: RationaleDetailed data on the characteristics and outcomes of patients with COVID-19 in sub-Saharan Africa are limited.ObjectiveWe determined the clinical characteristics and treatment outcomes of patients diagnosed with COVID-19 in Uganda.MeasurementsAs of the 16 May 2020, a total of 203 cases had been confirmed. We report on the first 56 patients; 29 received hydroxychloroquine (HCQ) and 27 did not. Endpoints included admission to intensive care, mechanical ventilation or death during hospitalisation.Main re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
55
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 22 publications
23
55
2
Order By: Relevance
“…This is much higher than a case fatality rate of 0·16% in children below 5 years of age in a recent large epidemiological study in Southern India [16]. Several other studies in China [26], Brazil [13,27], Uganda [14], and South Africa [15] have reported COVID-19-related deaths among children under 5 years to be rare. A review of data from US, Korea and Europe early in the epidemic estimated the overall case fatality rate among children (0-19 years old) to be low at 0·03 per 100 000 (44/42 846) [28].…”
Section: Discussionmentioning
confidence: 81%
“…This is much higher than a case fatality rate of 0·16% in children below 5 years of age in a recent large epidemiological study in Southern India [16]. Several other studies in China [26], Brazil [13,27], Uganda [14], and South Africa [15] have reported COVID-19-related deaths among children under 5 years to be rare. A review of data from US, Korea and Europe early in the epidemic estimated the overall case fatality rate among children (0-19 years old) to be low at 0·03 per 100 000 (44/42 846) [28].…”
Section: Discussionmentioning
confidence: 81%
“…This is much higher than a case fatality rate of 0.16% in children below 5 years of age in a recent large epidemiological study in Southern India [16] . Several other studies in China [29] , Brazil [13 , 30] , Uganda [14] , and South Africa [15] have reported COVID-19-related deaths among children under 5 years to be rare. A review of data from US, Korea and Europe early in the epidemic estimated the overall case fatality rate among children (0–19 years old) to be low at 0.03 per 100 000 (44/42 846) [31] .…”
Section: Discussionmentioning
confidence: 94%
“…However, most cases to date have occurred in low- and middle-income countries (LMIC) [11] , where differences in age distribution, comorbidities, access to quality health services, and other factors, may greatly influence trends regarding severe outcomes, but data are limited [12] , [13] , [14] , [15] , [16] , [17] . Indonesia is the fourth most populous country (population 274 million) and the LMIC that has suffered the highest number of COVID-19 confirmed cases and deaths in Southeast Asia, second only to India in Asia [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical outcomes reported in study participants included mortality, severe disease, hospitalization, length of hospitalization, the need for intubation, and development of acute respiratory distress syndrome. In one study, the final clinical outcome of patients was not reported (24).…”
Section: Resultsmentioning
confidence: 99%